Eminent Buddhist women - Karma Lekshe Tsomo, 1944- (State University of New York Press, 2014)
Explores the exemplary legacy of Buddhist women across the centuries and across the Buddhist world. Eminent Buddhist Women reveals the exemplary legacy of Buddhist women through the centuries. Despite the Buddha's own egalitarian values, Buddhism as a religion has been dominated by men for more than two thousand years. With few exceptions, the achievements of Buddhist women have remained hidden or ignored. The narratives in this book call into question the criteria for?eminence? in the Buddhist tradition and how these criteria are constructed and controlled. Each chapter pays a long-overdue tribute to one woman or a group of women from across the Buddhist world, including the West. Using a variety of sources, from orally transmitted legends to firsthand ethnographic research, contributors examine the key issues women face in their practice of Buddhist ethics, contemplation, and social action. What emerges are Buddhist principles that transcend gender: loving kindness, compassion, wisdom, spiritual attainment, and liberation.